Design of a low noise amplifier with GaAs MESFET at Ku-Band - Islam, Md. Rafiqul; Alam, A. H. M. Zahirul; Khan, Sheroz; Shabana, Arafat A. A (IEEE, 2010)
Ku-Band low noise amplifier has been designed with the gain of 8.90 dB and 2.19 dB noise figure for satellite receiver. The parameters are optimized by using Microwave Office Simulator (AWR) Ver. 2006. The size of the monolithic chip is 0.316mm2. The LNA is designed to operate at 12GHz.